Analysis Of Operational Risk Of Coffee Processing Factories In Perumda Perkebunan Kahyangan, Jember Regency - Prayogi, Muhammad Sabri; Prayuginingsih, Henik; Muliasari, Risa Martha (International Applied Science, 2024)
Jember Regency has a local coffee product, namely Kopi Kahyangan. Kahyangan Coffee is a ground and roasted coffee product produced by the Perumda Perkebunan Kahyangan Jember with coffee raw materials originating from Perumda's coffee plantations. Production risks can occur if they are not anticipated. The aim of this research is to analyze operational risks arising from processed coffee production activities at Perumda Perkebunan Kahyangan Jember and develop efforts to overcome them. The research results show that of the 8 types of risk, 2 risks have an extreme risk level that requires risk management with immediate countermeasures. 4 risks have a high risk level that requires senior management attention in overcoming them. 2 risks have a moderate risk level which requires determining management responsibility for overcoming them.